The consumption-based carbon footprint of households in Sulawesi, Jambi and Indonesia as a whole in 2013 - Mohammad Iqbal Irfany; Stephan Klasen; Rezky Syahrezal Yusuf (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
This study analyzes the consumption-based carbon footprint of households in Sulawesi, Jambi and Indonesia as a whole. Combining the use of the GTAP data for emission intensities, of input-output tables for inter-industry linkages with household expenditure categories, we then estimate and calculate the carbon footprint from household consumption, including its drivers, pattern and decomposition of increasing household emission intensities. We find that the main driver of carbon footprint is overall household income, but that differentials in fuel, light and transportation expenditures are key drivers of the household carbon footprint. These expenditures also ensure that the carbon footprint of household in Jambi is higher than in Indonesia as a whole, despite lower per capita incomes. At the same time, substantially lower income inequality in Jambi ensures that the inequality in the carbon footprint is much lower in Jambi than in Indonesia as a whole; particularly noteworthy is the poorer quintiles in Jambi have substantially higher emissions than average Indonesian households in the same quintiles. In Sulawesi, average emissions are much lower and also not as unequal than in Indonesia as a whole. Overall expenditures are by far the most important driver of household carbon emissions, but in Jambi, emissions are higher at all expenditure levels, suggesting particularly carbon-intensive consumption patterns.
Keywords: Q54; D12; O13; 330; development economics; carbon footprint; household emissions; comparison of Sulawesi; Jambi; and National SUSENAS